1) 4(0,6x-0,3)-3(0,7x-0,1)=0 2) 5(0,14-025x)+3(0,3x+0,1)=0 3) (1 3 - 2 3):1 3 4 8 5 4) (1 7 + 3 1)*5 15 3 12 5) (4 1 - 2 5)*(-1 3) 8 16 29
1) 4(0,6x-0,3)-3(0,7x-0,1)=0
2) 5(0,14-025x)+3(0,3x+0,1)=0
3) (1 3 - 2 3):1 3
4 8 5
4) (1 7 + 3 1)*5
15 3 12
5) (4 1 - 2 5)*(-1 3)
8 16 29
Ответ(ы) на вопрос:
1) 4(0,6x-0,3)-3(0,7x-0,1)=0
2,4x-1,2-2,1x+0,3=0
0,3x-0,9=0
0,3x=0,9
x=3
2) 5(0,14-0,25x)+3(0,3x+0,1)=0
0,7-1,25x+0,9x+0,3=0
-1,25x+0,9x=-0,7-0,3
-0,35x=-1
x=2,857 (если округлить, то получится 3)
3) [latex](1 \frac{3}{4}-2 \frac{3}{8}):1 \frac{3}{5} [/latex]
1) [latex] 1\frac{3}{4} -2 \frac{3}{8}= \frac{7}{4}- \frac{19}{8} \frac{28-19}{8}= \frac{9}{8} [/latex]
2) [latex] \frac{9}{8}: \frac{8}{5}= \frac{9*5}{8*8} = \frac{45}{64} [/latex]
4) [latex](1 \frac{7}{15}+3 \frac{1}{3})* \frac{5}{12} [/latex]
1)[latex]1 \frac{7}{15}+ 3\frac{1}{3}= \frac{22}{15}+ \frac{10}{3}= \frac{22+50}{15} = \frac{75}{15} [/latex]
2) [latex] \frac{75}{15}* \frac{5}{12}= \frac{75*5}{15*12}= \frac{25}{12} = 2\frac{1}{12} [/latex]
5) [latex](4 \frac{1}{8}-2 \frac{5}{16})*(- \frac{13}{29} ) [/latex]
1) [latex]4 \frac{1}{8}-2 \frac{5}{16} = \frac{33}{8}- \frac{37}{16}= \frac{66-37}{16} = \frac{29}{16} [/latex]
2) [latex] \frac{29}{16}*(- \frac{13}{29})=- \frac{29*13}{16*29}= - \frac{13}{16} [/latex]
Не нашли ответ?
Похожие вопросы